As alegorias religiosas de C. S. Lewis nas Crônicas de Nárnia = The religious allegories of C. S. Lewis in the Chronicles of Narnia - Silva, Heraldo Aparecido (Rever, 2020)
This article aims to analyze the religious allegories of the Chronicles of Narnia by C. S. Lewis. Initially, the study presents a brief distinction between the notions of cultural industry and pop culture to justify that the Narnia series’ literary and film versions are situated within the scope of pop culture. Then, the text presents the articulation between Lewis’ life and demonstrates that the author’s journey, which moved from atheism to conversion to Christianity, is reflected in the conception of his children’s fable. Finally, we argue that the experience of Christian life transmitted allegorically in the books and films of the Chronicles of Narnia attests to its longevity and relevance and contemplates pop culture’s main characteristics since it is innovative, critical archetypal, and provocative.